Origins of the COVID-19 pandemic and the path forward a global public health policy perspective (2020)
Although the world has experienced pandemics before, including several in the last fifteen years,1 the COVID-19 pandemic has caused an unprecedented global public health crisis. The synergy among multiple factors—including the relative ease of transmission of SARS-CoV-2, the failure to identify and contain early outbreaks of COVID-19, and the at times fraught relationship between political and public health priorities—has fundamentally jolted the world order. What began as a local outbreak in Wuhan, China, rapidly expanded to impact private and public sectors throughout the world, including governments at every level, across a host of domains. The phrase “COVID-19 crisis” has evolved to become shorthand for challenges to health care systems, labor markets, supply chains, and even geopolitics.